Delovaia khronika . Delovaia khronika . Business Chronicle . Деловая хроника - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Russia's transition to market prices; the announcement of the currency exchange rate. Featured in the program: Yeltsin, Boris Nikolayevich (President of the Russian Federation) Contributors: TSvetkova, Ekaterina (Anchor) Переход России на мировые цены, объявление курса обмена валют. В программе участвуют: Ельцин, Борис Николаевич (Президент Российской Федерации) Создатели: Цветкова, Екатерина (Ведущий/Ведущая)